Association between axial length and level of education in elderly patients with cataracts unexposed to electronic devices in the first two decades of life - Reis,Roberto dos (2022)
ABSTRACT Purpose: To determine whether the axial length is associated with the education level in elderly patients with cataracts who were not exposed to electronic devices in the first two decades of life. Methods: This cross-sectional study was conducted in elderly patients with cataracts in Campinas, Brazil. Patients were divided into 2 groups: Group 1 included those who completed, at most, elementary school (including the illiterate and those who partially or totally attended elementary school), which corresponded to 12 years of schooling; Group 2 included, at least, high school graduates (including those who completed high school and those who partially or fully attended university). The sample was selected randomly with stratification for sex and age. The main outcome was the axial length. Results: The sample consisted of 472 elderly patients (236 per group) who underwent cataract surgery. There were 272 (57.6%) men and 200 (42.4%) women; the distribution was symmetrical between the two groups. The median age (IQR; range) was 66 (12; 50-89) years. The median axial length (IQR; range) was 22.82 (1.51; 20.34-28.71) mm in Group 1 and 23.32 (1.45; 20.51-31.34) mm in Group 2 (p<0.001). Conclusion: A greater axial length was associated with a higher level of education in elderly patients with cataracts, suggesting that myopization is related to an increase in activities requiring near-vision even before exposure to electronic devices.